A COMPARATIVE LOOK AT THE POEMS OF MEHMET AKIF ERSOY AND ABAY KUNANBAYEV - Soilemez, O.; Atesh, O. F. (Dulaty University, 2024)
Türkiye and Kazakhstan have entered the modernization process since the late 19th century. Accordingly, in both regions, writers and poets reflected the need for reform in their works, and literary works focused on social problems. Abay Kunanbayev and Mehmet Akif exhibited a similar attitude in terms of including social criticism and emphasizing the need for innovation. The fact that both artists criticize unfair rulers, laziness and ignorance, and emphasize the women's issue is an indication of this attitude. In this article, the poems of Abay Kunanbayev and Mehmet Akif will be discussed comparatively.
Keywords: 10. No inequality